2001
DOI: 10.1007/s002280100353
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and non-analgesic effects of S- and R-ketamines in healthy volunteers with normal and reduced metabolic capacity

Abstract: There are large differences between arterial and venous data in the pharmacokinetic parameters that are heavily dependent on distribution processes. Parameters mainly reflecting elimination, such as clearance and area under the concentration time curve, are unchanged. The choice of sampling site could be important when computer-controlled infusions are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 27 publications
7
44
0
Order By: Relevance
“…In vivo studies in humans have shown higher values for the clearance of S-ket than for R-ket either after administration of the individual enantiomers (Persson et al, 2002;White et al, 1985) or after administration of the racemic mixture (Henthorn et al, 1999;Geisslinger et al, 1993;Ihmsen et al, 2001). Our results also clearly show differences in biotransformation of ketamine and/or norketamine enantiomers resulting in consistently higher plasma concentrations of S-nor than of R-nor.…”
Section: Discussion Pharmacokineticssupporting
confidence: 57%
“…In vivo studies in humans have shown higher values for the clearance of S-ket than for R-ket either after administration of the individual enantiomers (Persson et al, 2002;White et al, 1985) or after administration of the racemic mixture (Henthorn et al, 1999;Geisslinger et al, 1993;Ihmsen et al, 2001). Our results also clearly show differences in biotransformation of ketamine and/or norketamine enantiomers resulting in consistently higher plasma concentrations of S-nor than of R-nor.…”
Section: Discussion Pharmacokineticssupporting
confidence: 57%
“…The pathways involved in the metabolism of ketamine have been of interest particularly in view of the pronounced polymorphisms of enzymes such as CYP2D6 and CYP2C19 [22]. Updates, primarily on animal and in-vitro data, identify CYP2B6, CYP3A4 and to a lesser extent CYP2C9 as the main enzymes metabolizing ketamine [26,27].…”
Section: Enantiomersmentioning
confidence: 98%
“…It has been well established that the elimination clearance of S-ketamine is larger than that of R-ketamine. The volume of distribution of the central compartment and at steady state might also be larger [22]. The S-form has been commercially available for several years, probably based on the perception that it would have a better effect to side-effect ratio [23].…”
Section: Enantiomersmentioning
confidence: 99%
“…The patients were shown to have reduced metabolic capacity on the basis of phenotype data using the oxidative pathways of model substrates debrisoquin (CYP2D6) and mephenytoin (CYP2C19) (Persson et al, 2002). Based on the data gathered in this study, it was shown that pharmacokinetics of individual enantiomers of ketamine in normal subjects and subjects with impaired CYP isozymes were similar.…”
Section: Ketaminementioning
confidence: 97%
“…Based on the data gathered in this study, it was shown that pharmacokinetics of individual enantiomers of ketamine in normal subjects and subjects with impaired CYP isozymes were similar. Interestingly, the arterial kinetic parameters (volume of distribution; MRT) for the two enantiomers of ketamine showed differences when compared with the intravenous kinetic parameters (Persson et al, 2002).…”
Section: Ketaminementioning
confidence: 99%